Analisis Majas Persamaan, Metafora, dan Personifikasi Novel Jantera Bianglala Karya Ahmad Tohari - Emi Priyanti; Dendy Sugono; Hasbullah Hasbullah (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2023)
Analysis of Simile, Metaphor, and Personification in Ahmad Tohari's Novel Jantera Bianglala. This study aims to describe sentences that have simile, metaphor, and personification in the novel Jantera Bianglala by Ahmad Tohari. This qualitative descriptive research uses sentence analysis technique. The research covers sentence data in the novel, data presentation, and draws conclusions about the types of figures of speech and their number. The result of this research analysis shows that there are 37 sentences with figure of speech similes/associations. There are 34 metaphorical sentences with 36 metaphors. There are 102 sentences in personification with 159 personifications. There is one sentence which has one to five figures of speech, some are of one type, and some are a combination of the figures of speech studied. Most of the figure of speech found is personification.Keywords: Simile, Metaphor, Personification,Novel Jantera Bianglala